Barriers for big data integration to the financial statement audit procedures - Raziūnienė, Daiva; Čirba, Karolis (Buhalterinės apskaitos teorija ir praktika, 2021)
An application of the most inovative technologies of the big data processing is the high challenge for financial statement auditors. The term “big data” refers to large amount of digital data that may be used to reveal issues, prospective and relations of human behaviour and actions. For instance, international and national audit companies are using big data analytics to identify risk and fraud during audits. The purpose of the article is to identify barriers to the integration of big data into external financial audit procedures. The object of the research is big data models and their components. Tasks formulated to achieve the goal: 1) after examining the concept of big data presented by various authors, to determine the role of big data in the audit of external financial statements; 2) to identify the factors that hinder the integration of big data into audit evidence collection procedures. Research methods used in the article include the content analysis of scientific literature.